Implementation of GSM based Flood Data Communication in the Flood Disaster Location Information System. (April 2019) - Satria, Dedi; Yana, Syaifuddin; Munadi, Rizal; Syahreza, Saumi; Munawir
Abstract: The frequency of floods that often occur in Indonesia has made floods one of the national disasters designated as national priorities. The flood disaster has caused many casualties and material losses. For the government to anticipate more flood victims, a flood information system is needed that can provide real-time flood information in the form of location information and the level of flood level. Based on these problems, this research article aims to build a flood disaster information system in real-time location-based information using data communication based on Global System for Mobile Communications (GSM). The system design is built in two systems, namely the client system or flood detector consisting of ultrasonic sensor components as input modules, Arduino Uno microcontrollers as processing modules and SIM900 modules as output components. Next is a server system consisting of Wavecom GSM Modem as input component and PHP Engine software, mySQL database, Apache Web Server as data processing. In processing flood information, the client system sends location and water level data using SIM900 in the form of SMS to the server system. The server system processes the data so that it produces information on the location and height of the flood that can be distributed through the website. This study produced a location-based flood disaster information system prototype with data communication between flood detectors and flood information system servers using Global System for Mobile Communications (GSM) media.